An exergoecological analysis of the mineral economy in Spain. (August 2015) - Calvo, Guiomar; Valero, Alicia; Valero, Antonio; Carpintero, Óscar
Abstract: This paper shows how exergy can be used to assess the mineral balance of a country and at the same time assess its mineral resource sustainability. The advantage of using such an approach is that the quality of the resources is taken into account, as opposed to the conventional procedure that uses tonnage as a yardstick. The exergoecology method evaluates mineral resources as the exergy required to replace them from a complete dispersed state to the conditions they were originally found with the best available technologies. The country chosen as a case study is Spain and serves as a representative example of the mineral situation in Europe. The general trend observed is that imports are increasing and domestic production is decreasing. The minerals with higher exergy replacement costs are mainly those imported, including fossil fuels and scarce minerals. In 2005, the domestic production of minerals was higher than the imports but since imports were mainly of scarce minerals, the exergy loss associated with such imports was higher compared to domestic production. As it happens to most European nations, Spain is a very dependent country regarding the supply of fossil fuels but not as much in the case of non-fuel minerals. Highlights: Exergy analysis is used to assess the mineral balance of a country. The advantage of using exergy analysis is to account for resource quality. Spain is used as a representative country for Europe's mineral trade. Mineral trade in Spain from 1995 to 2010 is analyzed.